Figuras del exilio rumano con proyección europea: Ciorănescu, Eliade, Vișniec. El caso de Mircea Eliade: Figures of Romanian exile with European projection: Ciorănescu, Eliade, Vișniec. The case of Mircea Eliade - Diz Villanueva, Alba (Swedish Journal of Romanian Studies, 2023)
Within the framework of the Seminar ”Romanian Exile and Migration: Cultural Representations in Europe”, the aim of this work is to illustrate, through the diaries of Mircea Eliade, the reasons and circumstances in which the Romanian writer and historian of religions leaves his country, the different stages and destinations of his exile, the literary and scientific contributions made by him in this context, as well as the reflections that the author makes about his own situation and about this phenomenon.